PROTECTION OF CHILDREN'S DATA ON THE INTERNET: LEGAL AND POLICY ASPECTS - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (ADISAM PUBLISHER, 2025)
The protection of children's data on the internet is becoming an increasingly crucial issue as the use of digital technology by children increases. This study explores various legal and policy aspects designed to protect children's personal data in the digital realm. In the legal context, this document discusses regulations adopted by various countries, such as the Children's Online Privacy Protection Act (COPPA) in the United States, which requires parental consent for the collection of data on children under a certain age. In addition, the policies implemented by governments, technology companies, and educational institutions are outlined to demonstrate how multisectoral collaboration can strengthen the protection of children's data. The main findings highlight the importance of public education and consistent implementation of existing policies as the key to creating a safer online environment for children. The study concludes with policy recommendations to improve the framework for the protection of children's data, including the need for strict sanctions against violations and the importance of raising awareness about digital privacy